2020
DOI: 10.34190/ejel.20.18.2.004
|View full text |Cite
|
Sign up to set email alerts
|

e‑Learning Challenges Faced by Universities in Kenya: A Literature Review

Abstract: Some institutions of higher education in Kenya have adopted e‑Learning with the aim of coping with the increased demand for university education and to widen access to university training and education. Though there are advantages that accrue from adopting e‑Learning; its implementation and provision has not been smooth sailing. It has had to contend with certain national, organisational, technical and social challenges that undermine its su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 6 publications
(7 reference statements)
1
24
0
Order By: Relevance
“…This was compounded by the fact that sometimes the e-learning system loads too slow, leading to some students aborting their attempts to use it. The issue of costs has been identified as a major factor impeding successful e-learning implementation in developing countries (Kibuku et al 2020), including in Namibia (Ilonga et al 2020). Similarly, Aboagye, Yawson and Appiah (2020) identified accessibility as the most important challenge facing students in Ghana during the Covid-19 pandemic.…”
Section: Theme 3 -Resources To Access To Internet and Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…This was compounded by the fact that sometimes the e-learning system loads too slow, leading to some students aborting their attempts to use it. The issue of costs has been identified as a major factor impeding successful e-learning implementation in developing countries (Kibuku et al 2020), including in Namibia (Ilonga et al 2020). Similarly, Aboagye, Yawson and Appiah (2020) identified accessibility as the most important challenge facing students in Ghana during the Covid-19 pandemic.…”
Section: Theme 3 -Resources To Access To Internet and Networkmentioning
confidence: 99%
“…Student perceptions are an important aspect of e-learning success, yet there is a paucity of studies on challenges faced by these key stakeholders when using e-learning in the Namibian higher education context (Woyo, Rukanda and Nyamapanda, 2020), particularly in the unusual environment created by the COVID-19 pandemic. E-learning has historically tended to be too technologically centered, with the inevitable consequence of institutions of learning overemphasizing the technologies to the detriment of other factors (Kibuku, Ochieng & Wausi, 2020). It is axiomatic that e-learning success is more than just access to the technology.…”
Section: Introductionmentioning
confidence: 99%
“…Other barriers that also hinder innovative use of ICT include "lack of confidence, experience, motivation, and training; access to resources and timetabled use of dedicated ICT classrooms; unreliability of equipment; classroom practices which clash with the culture of student exploration, collaboration, debate, and interactivity within which much technology-based activity is said to be situated" ( [27], p. 28). Indeed, lack of online pedagogical skills of teachers and students, negative attitude about online learning, over emphasis on technology at the expense of learning, lack of support for online learning [28] and the COVID-19 pandemic have also compromised the progress made by majority of HEIs in Africa in their effort to embrace the new normal to support online pedagogy.…”
Section: Barriers Hindering Africa's Heis To Embrace Ict In Teaching and Learningmentioning
confidence: 99%
“…Also applying e-learning includes some challenges, such as the lack of teacher's online teaching skills, online preparation for lesson plans because it takes too long, lack of adequate support from technical teams, pressure in the use of online educational platforms, and an inadequate ICT infrastructure. In addition to the lack of: appropriate e-learning policies, technical and educational competencies and the training of e-teachers and e-learners, elearning theory to support the practice of e-learning, and sustainability issues, negative perceptions towards e-learning, quality issues, (Kibuku et al, 2020& Soni, 2020. Alqahtani & Rajkhan (2020) confirmed that the most influencing factors in e-learning success during the Corona pandemic are technology management and support from the administration, increasing students 'awareness of using e-learning systems, and demanding a high level of information technology from trainers, students and educational institutions.…”
Section: Ijher Journal International Journal Of Humanities and Educational Researchmentioning
confidence: 99%